Autism and managing anxiety : practical strategies for working with children and young people - Middletown Centre for Autism (Middletown, Northern Ireland) (Abingdon, Oxon ; New York : Routledge, 2020)
"This easy-to-use resource is a compilation of practical, evidence-based strategies, interventions and whole-school approaches designed to support teachers and parents who are working with or caring for children and young people with autism experiencing anxiety. Using real life examples and case studies, the book explains and explores the different forms of anxiety, and their impact on the lives of young people with autism. Each chapter offers practical information and strategies that will effectively reduce the negative symptoms of anxiety and help support emotional resilience across home and school environments. Key features of this book include: Chapters exploring the background and theory of anxiety in children and young people with autism, considering the prevalence, causes and triggers of anxiety, cognitive theories, social communication and means of assessing anxiety. A wealth of downloadable anxiety management strategies and resources that can be adapted and used with individuals or groups of varying ages. Developed by a team at the renowned Middletown Centre for Autism, this is an invaluable resource for the busy parent or teacher, along with other professionals looking to support children and young people with autism and anxiety"--
Introduction : autism and anxiety -- Social communication, autism and anxiety -- Cognitive theories, learning style, autism and anxiety -- Sensory processing, autism and anxiety -- Assessment of anxiety in autism -- Anxiety management strategies for autistic children and young people.
OCLC-licensed vendor bibliographic record.
Keywords: Autistic children -- Education; Children with autism spectrum disorders -- Education; Autism in children; Autism spectrum disorders in children; Anxiety in children; Anxiety disorders; EDUCATION / General